Calcification reduction and recovery in native and non-native Mediterranean corals in response to ocean acidification - Movilla, Juan Ignacio; Calvo, Eva María; Pelejero, Carles; Coma, Rafael; Serrano, Eduard; Fernández-Vallejo, Pilar; Ribes, Marta (Journal of Experimental Marine Biology and Ecology, 2012)
10 páginas, 7 figuras, 2 tablas. In recent years, some of the ramifications of the ocean acidification problematic derived from the anthropogenic rising of atmospheric CO2 have been widely studied. In particular, the potential effects of a lowering pH on tropical coral reefs have received special attention. However, only a few studies have focused on testing the effects of ocean acidification in corals from the Mediterranean Sea, despite the fact that this basin is especially sensitive to increasing atmospheric CO2. In this context, we investigated the response to ocean acidification of the two zooxanthellate coral species capable of constituting the main framework of the community, the endemic Cladocora caespitosa and the non-native Oculina patagonica. To this end, we examined the response of both species to pCO2 concentrations expected by the end of the century, 800 ppm, vs the present levels. Calcification rate measurements after 92 days of exposure to low pH conditions showed the same negative response in both species, a decrease of 32–35% compared to corals reared under control conditions. In addition, we detected in both species a correlation between the calcification rate of colonies in control conditions and the degree of impairment of the same colonies at low pH. Independent of species, faster growing colonies were more affected by decreased pH. After this period of decreased pH, we conducted a recovery experiment, in which corals reared in the acidic treatment were brought back to control conditions. In this case, normal calcification rates were reached in both species. Overall, our results suggest that O. patagonica and C. caespitosa will both be affected detrimentally by progressive ocean acidification in the near future. They do not display differences in response between native and non-native species but do manifest differential responses depending on calcification rate, pointing to a role of the coral genetics in determining the response of corals to ocean acidification. Financial support for ...